Does Gd-EOB-DTPA–enhanced T1 mapping have a role in the staging of fibrosis and inflammation in autoimmune hepatitis? A prospective study. - Torres, Ulysses S.; Gomes, Natália B. N.; Caiado, Angela H. M.; Fucuta, Patricia S.; Ferraz, Maria Lucia C.G.; D'Ippolito, Giuseppe (Abdominal Radiology, 2026)
Objectives: Autoimmune hepatitis (AIH) is an immune-mediated liver disease that may progress to cirrhosis if untreated. Liver biopsy is the gold standard for assessing fibrosis and inflammation, but it is invasive and prone to sampling errors. This prospective study evaluated whether MRI T1 mapping with gadoxetic acid (Gd-EOB-DTPA) can noninvasively predict fibrosis stage and inflammatory activity in AIH. We compared several post-contrast T1 mapping-derived formulas to determine accuracy in detecting significant (F2–F4) and advanced (F3–F4) fibrosis and higher inflammatory activity (PPA 2–4). Materials & methods: Over three years, 33 AIH patients underwent a multiparametric liver MRI protocol with post-Gd-EOB-DTPA T1 mapping. Biopsies were performed up to three months prior. We measured standard pre- and post-contrast T1, adjusted liver T1 formulas, and hepatic uptake rates (Khep). Independent t-tests, Mann-Whitney U-tests, and ROC curves compared these indices against Metavir (F0–F4) and Desmet inflammatory grading (PPA 0–4). Results: Post-contrast T1 at 20 min (AUC 0.822; 95% CI 0.674–0.970) and a mathematical formula (Adjusted T1 Liver B) (AUC 0.815; 95% CI 0.660–0.970) distinguished advanced (F3–F4) from non-advanced (F0–F2) fibrosis. However, none of the MRI-based parameters differentiated significant fibrosis (F2–F4) or higher inflammatory grades (PPA 2–4) from lower ones. Post-contrast T1 mapping did not outperform simpler pre-contrast T1 measurements (p > 0.05). Conclusion: In AIH, post-Gd-EOB-DTPA T1 mapping within a standard liver MRI protocol can identify advanced fibrosis, correlating well with the histopathological gold standard. However, it does not outperform simpler pre-contrast T1 measurements or reliably distinguish significant fibrosis or severe inflammation.